MINAT PESERTA DIDIK TENTANG STUDI LANJUT KE PERGURUAN TINGGI KELAS XII SMA ISLAM BAWARI - Azzahrah, Dessy; Astuti, Indri; Yuline, Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis reseach aimed to determine the interest of students about further study to University in class XII Sma Islam Bawari Pontianak. The method in this reseach was descriptive method with the form of reseach used survey. The population ini this study were 139 and the samples were 86 students off class XII. The techniques and tools used in this reseach were indirect communication techniques with questionnaire tools modifed form Kuder?s test. Based on the result of the analysis of data on the interest of students about further studies to university that studens? are more interested in university. The results showed that the interest of students to university was 76% in the ?high? category, while the interest of students to insitutes was 5% in the ?low? category, as for the interest of students to the academy is 2,32% with the category ?low? and students? interest in polytechnics at 8% with a low category. Then it can be concluded that in this study the interest of students can already be seen, namely students of class XII Sma Islam Bawari Pontianak have a greater interest in universities with high ctegories.Keywords: Advanced study to University, Interest